Nicotine self-administration with menthol and audiovisual cue facilitates differential packaging of CYP2A6 and cytokines/chemokines in rat plasma extracellular vesicles - Asit Kumar (Nature Portfolio, 2021)
Abstract In this study, we investigated whether intravenously self-administered nicotine with menthol and audiovisual cue modulates nicotine-metabolizing CYP2A6, oxidative stress modulators, and cytokines/chemokines in plasma extracellular vesicles (EVs) in rats. We assigned rats to self-administered nicotine with: (a) audiovisual cue (AV), (b) menthol, and (c) menthol and AV cue. We found increased levels of CD9 in plasma EVs after self-administered nicotine with menthol and AV cue. Moreover, expression of CYP2A6 in plasma EVs was significantly increased after self-administered nicotine in response to menthol and AV cue. However, despite an upward trend on SOD1 and catalase, increase was not found to be statistically significant, while total antioxidant capacity was found to be significantly increased in plasma and plasma EVs obtained after self-administered nicotine with menthol and AV cue. Among cytokine and chemokine profiling, we found a significant increase in the levels of MCP-1 after self-administered nicotine with menthol and AV cue and complete packaging of IL-1β in EVs. Taken together, the study provides evidence that nicotine in response to menthol and AV cues can package altered levels of CYP2A6, and cytokines/chemokines in plasma EVs that may contribute to cell–cell communication, nicotine metabolism, and inflammation upon cigarette smoking.